RESPON KECEMASAN PADA LANSIA YANG DIBERIKAN TERAPI RELAKSASI NAFAS DALAM - Khorida Alvima Maul Jannah; Dyah Widodo; Widiani, Esti (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
The elderly is someone who has entered retirement or is 60 years old and is characterized by a period of deterioration of body cells, including movement and memory, which can make an older person often feel anxiety or anxiety about the life that will be passed next. One way for anxiety to decrease or disappear is by doing deep breath relaxation therapy because it is considered adequate and accessible. Deep breath relaxation is done with a deep breath technique of approximately 5 seconds, then exhaling slowly. The purpose of this study was to identify the description of anxiety responses in older people who were given deep breath relaxation therapy. The research method uses a case study approach with 2 elderly subjects. Anxiety data was collected using interview sheets, observation sheets, and Geriatric Anxiety Scale (GAS) questionnaires. The results showed that subjects who were given a deep breath relaxation therapy intervention for 2 weeks with 6 meetings experienced a decrease in anxiety from moderate anxiety to mild anxiety; subject 1, with a middle anxiety score of 41, decreased to mild anxiety with a score of 24 while subject 2 experienced moderate anxiety with a score of 43 reduced to mild anxiety with a score of 27. It is hoped that what has been taught (deep breath relaxation) can be done regularly to maintain anxiety levels so that they can manage anxiety independently.